ANALISIS DAMPAK EKONOMI MAKRO DAN RATE OF RETURN SAHAM IDX VALUE30 TERHADAP INDEKS SEKTOR PORPERTI, REAL ESTATE DAN KONSTRUKSI DI TENGAH PANDEMI COVID-19 - Reynaldo Sihite (2022)
The objective of this reaserch is to analyze the influence of macroeconomic variables: exchange rate USD/IDR exchange rate, inflation, BI rate, golden future price, and rate of return of IDX Valuue30 Stock's on The Property, Real Estate and Construction Index (IDXPROP) August 2019 - April 2021 Period (Monthly Data). This study uses a quantitative approach with multiple linear regression analysis. The result of this study is macroeconomic variables simultaneously influenced IDXPROP August 2019 - April 2021 Period. On partial impact, exchange rate USD/IDR exchange rate and golden future price have influenced negative and significant towards IDXPROP. Inflation and rate of return of IDX Valuue30 Stock's have influenced negative and insignificant towards IDXPROP. BI Rate has influenced negative and insignificant towards IDXPROP. Investors can pay attention to movements in the USD/IDR exchange rate and gold futures prices in formulating an investment strategy in IDXPROP, Investors can invest in IDXPROP when the USD/IDR exchange rate and gold price are expected to weaken. Companies in the Property, Real Estate, and Construction sectors can pay attention to movements in the USD/IDR exchange rate and gold futures prices in planning company strategies.